2021
DOI: 10.3390/molecules26123755
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Green Tea Polyphenols

Abstract: Green tea and its bioactive components, especially polyphenols, possess many health-promoting and disease-preventing benefits, especially anti-inflammatory, antioxidant, anticancer, and metabolic modulation effects with multi-target modes of action. However, the effect of tea polyphenols on immune function has not been well studied. Moreover, the underlying cellular and molecular mechanisms mediating immunoregulation are not well understood. This review summarizes the recent studies on the immune-potentiating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 116 publications
(202 reference statements)
0
47
0
Order By: Relevance
“…TP, especially EGCG and ECG, can significantly enhance the immune response and reduce the risk of inflammation and immune-related diseases [ 85 , 86 ]. As a natural immunomodulator, TP can deal with immune system diseases by up-regulating or down-regulating the immune response without adverse effects such as pro-inflammatory responses [ 87 ]. In the human body, T helper cell (Th)1 and Th2 are important members of cellular immunity and humoral immunity, respectively.…”
Section: Immunomodulatory Effects Of Tp-mediated Gut-lung Axis On Cov...mentioning
confidence: 99%
See 1 more Smart Citation
“…TP, especially EGCG and ECG, can significantly enhance the immune response and reduce the risk of inflammation and immune-related diseases [ 85 , 86 ]. As a natural immunomodulator, TP can deal with immune system diseases by up-regulating or down-regulating the immune response without adverse effects such as pro-inflammatory responses [ 87 ]. In the human body, T helper cell (Th)1 and Th2 are important members of cellular immunity and humoral immunity, respectively.…”
Section: Immunomodulatory Effects Of Tp-mediated Gut-lung Axis On Cov...mentioning
confidence: 99%
“…In addition to antiviral therapy, anti-inflammatory therapy that suppresses cytokine storm is essential to reduce mortality in patients with COVID-19. IL-6 is often elevated in patients with COVID-19, and its level is positively correlated with COVID-19 mortality [ 87 , 99 ]. Persistent cytokine storm increases the alveolar vascular permeability, the body fluid and blood cells enter the alveoli, resulting in pulmonary edema, ARDS, and even respiratory failure [ 100 , 101 ].…”
Section: Immunomodulatory Effects Of Tp-mediated Gut-lung Axis On Cov...mentioning
confidence: 99%
“…These findings imply that pretreatment with the J. effusus L. water extract reduces the innate immune response by blocking the binding sites on oral epithelial cells for TLR2 and TLR4 ligands, suggesting that the J. effusus L. water extract may be beneficial in the prevention of innate immune responses that leads to periodontal tissue inflammation. It has been reported that EGCG inhibits intracellular signal transduction pathways and ultimately suppresses the transcription of various inflammation-related mediators [ 44 46 ]. This study indicated that pretreatment with J. effusus L. water crude extract suppressed the expression and production of chemokine genes by inhibiting the binding of TLR ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, factors that limit the activation of NF-κB may also prevent the expression of cytokines, and consequently block inflammatory response. EGCG inhibits the activation of NF-κB and MAPK as well as the expression of IFNγ, TNF-α, and IL-1β, while also stimulating the innate expression of immunity-related genes (e.g., TNF-α, MAPK, NOS) and inhibiting apoptosis [135]. EGCG may also inhibit the infiltration of inflammatory and pro-inflammatory leukocytes IL-8, while studies on mice revealed that it can lower the expression of pro-inflammatory factors: NF-κB and IL-6 [135][136][137].…”
Section: Anti-inflammatory and Immunomodulatory Propertiesmentioning
confidence: 99%
“…EGCG inhibits the activation of NF-κB and MAPK as well as the expression of IFNγ, TNF-α, and IL-1β, while also stimulating the innate expression of immunity-related genes (e.g., TNF-α, MAPK, NOS) and inhibiting apoptosis [135]. EGCG may also inhibit the infiltration of inflammatory and pro-inflammatory leukocytes IL-8, while studies on mice revealed that it can lower the expression of pro-inflammatory factors: NF-κB and IL-6 [135][136][137]. Thichanpiang and Wongprasert [118] demonstrated that EGCG shows anti-inflammatory effects on human retinal pigmented epithelial cells ARPE-19, partially as a suppressor of TNF-α signaling, and that the inhibitive effects occur along the NF-κB pathway.…”
Section: Anti-inflammatory and Immunomodulatory Propertiesmentioning
confidence: 99%